A well-testing model for partially perforated wells in natural gas hydrate reservoirs - Chen, Yu; Zhou, Yunjian; He, Yufa; Fu, Qiang; Li, Peihuan; Qi, Peng; Fang, Xing (Frontiers in Energy Research, 2024)
Natural gas hydrates (NGH) are considered as a very promising source of clean energy due to their widespread distribution, high energy density, and pure combustion products. Currently, there are few studies on NGH reservoir well testing, and the models are often idealistic, lacking practical guidance for field application. In this paper, a well testing model for partially perforated wells in the NGH reservoir is proposed, which takes into account the dynamic decomposition of hydrates. This model can simulate the performance of the perforated NGH well with a dynamic dissociation interface, which divides the reservoir into decomposed and undecomposed regions. Governing equations in cylindrical coordinates is formulated to depict fluid flow. Moving boundaries and dissociation coefficients are incorporated to describe the solid-to-gas transition within hydrates. Analytical solutions including pressure transient behaviors of the NGH reservoir and the bottomhole pressure (BHP) of partially perforated wells are derived, by utilizing the Laplace transform, method of separation of variables and Stehfest numerical inversion algorithm. Sensitivity analysis is conducted using the parameters from partially perforated wells and NGH formation properties. We plot pressure and pressure derivative curves in double logarithmic coordinates to study the pressure transient behaviors. There are seven flow regimes that are typical for partially perforated wells in the NGH reservoir, including pure wellbore storage, skin effect, spherical flow, pseudo-radial flow, composite effect, improvement and radial flow regimes.